The Acceptance of Utilizing Low-density Polyethylene (LDPE) Plastic in Concrete Brick Among Construction Stakeholders - Mohd Noh, Hamidun; Abu Bakar, Nurul Fatin Nazwa; Idris, Nur’ain; Kasim, Narimah; Zainal, Rozlin; Shareh Musa, Sharifah Meryam (Research in Management of Technology and Business, 2021)
Concrete bricks are the basic material and an important element for all types of construction. Recently, the problem faced by the construction industry is the demand for concrete bricks is increasing along with the price of the materials. In this study, low-density polyethylene (LDPE) was selected as a substitute for fine sand material in brick making. Recycling features that can use the cost of materials are the main reason for the use of the LPDE. In addition, the use of LDPE will help the source of pollution by the millions of plastic wastes accumulated at landfills. In addition, this material is available with a high degree of durability and weather resistance. This study was conducted to see the potential to produce the replacement of LDPE plastic waste in concrete brick manufacturing in Malaysia. The objective of this study is to identify the factors that influence the choice of materials in brick manufacturing, to investigate the potential acceptance of this product using LDPE plastic waste in brick manufacturing, and to identify the initiative in managing LDPE plastic waste and improving the brick products. An interview has conducted with the parties involved in the recycling of LDPE plastic waste and among the target respondents for this study are individuals who carry out work related to the management of plastic waste recycling and bricks industry manufacturing. Then the results of the interview will be analyzed and formulated to archive the objective of the study. For objective one, shows that have two factor that can be the main factor to influence the choice of materials in brick manufacturing which is factor on cost and technology. Next for objective two, shows that this product using LDPE plastic has the potential to be marketed in industry because the use of waste product material in concrete that is good alternative and environmentally friendly. Last objective shows by reusing the plastic, it can protect our environment and also reduce pollution. This research can contribute to the environment and waste material in concrete brick. This is also can suggest the construction stakeholder on the alternative material that potentially replace aggregate in concrete to produce the brick product with eco-friendly.